2020
DOI: 10.1002/ijc.33442
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of oral HPV infection: Longitudinal analyses in prospective cohorts from Australia

Abstract: Oral infection with human papillomavirus (HPV) is likely to underpin the rapidly rising incidence of oropharyngeal squamous cell carcinoma; however, there are few data describing the natural history of oral HPV infection. We recruited 704 participants aged 20 to 70 years from worksites, universities and primary care practices in Brisbane, Australia. Participants completed questionnaires at baseline, 12 and 24 months and donate four saliva samples at baseline, 6, 12 and 24 months for HPV polymerase chain reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 28 publications
6
27
2
Order By: Relevance
“…In a more recent study on over 3000 HIM participants, 10-30% of oral High-risk HPV infections were found to persist beyond 24 months (18% in the case of HPV16) [102]. A very recent study conducted in Australia showed that around one quarter of the individuals that were HPV-negative at baseline acquired new Alpha-HPV infections over a 24-month period [25].…”
Section: Natural Historymentioning
confidence: 99%
See 1 more Smart Citation
“…In a more recent study on over 3000 HIM participants, 10-30% of oral High-risk HPV infections were found to persist beyond 24 months (18% in the case of HPV16) [102]. A very recent study conducted in Australia showed that around one quarter of the individuals that were HPV-negative at baseline acquired new Alpha-HPV infections over a 24-month period [25].…”
Section: Natural Historymentioning
confidence: 99%
“…Saliva samples are usually shaken and incubated at 50 • C-56 • C for 1-2 h before nucleic acid extraction [25][26][27][28]. Oral rinse-and-gargles are obtained with 10-15 mL of commercial mouthwashes, buffer saline or water, used for rinse and gargle cycles of 30-60 s. In the pre-analytic phase, these samples are centrifuged (at least at 2000 rpm for 10 min) to obtain the cell pellet.…”
Section: Sample Collection Nucleic Acid Extraction and Purificationmentioning
confidence: 99%
“…21 Antonsson and colleagues described a longitudinal study (0, 6, 12 and 24 months) of 704 people from Brisbane (18-70 years old). 32 They reported an oral HPV prevalence of 10.7% (high-risk HPV prevalence 6.4%) at baseline in 636 people who tested positive for β-globin. 33 In our study, the most prevalent HPV types at baseline were those associated with Heck's disease (23% of the HPV types found); a relatively benign and rare condition caused by oral HPV types 13 or 32 that appears to be more prevalent among Indigenous populations around the world.…”
Section: Open Accessmentioning
confidence: 99%
“… 21 Antonsson and colleagues described a longitudinal study (0, 6, 12 and 24 months) of 704 people from Brisbane (18–70 years old). 32 They reported an oral HPV prevalence of 10.7% (high-risk HPV prevalence 6.4%) at baseline in 636 people who tested positive for β-globin. The International Agency for Research on Cancer’s (IARC) definition of high-risk HPV was used: HPV 16, HPV 18, HPV 31 to HPV 33, HPV 35 to HPV 39, HPV 45 to HPV 51, HPV 52, HPV 56, HPV 58, HPV 59 to HPV 66.…”
Section: Findings To Datementioning
confidence: 99%
“…The current therapy is only effective for early stage OSCC, and the 5-year overall survival rate was <50% in 2020 ( 2 ). Studies have indicated that tobacco addiction, excessive alcohol consumption and human papillomavirus (HPV) infection are the main risk factors for tumorigenesis and the development of OSCC ( 3 ). Current targeted therapies, such as targeting PD1/PDL1, are far from satisfactory ( 4 ); therefore; new predictive biomarkers and therapeutic targets are urgently required.…”
Section: Introductionmentioning
confidence: 99%